Analysis of Formulation and Implementation Preparation: Waste to Energy Plant Development Policy in Surakarta City - Ayuningtyas, Tiara Kusuma; Nurharjadmo, Wahyu (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2021)
The problem of waste as an urgent problem in Surakarta became the beginning of the idea the Waste to Energy of PLTSa Development in Putri Cempo Landfill. This study aims to describe the process of policy formulation and analyze the implementation preparation of PLTSa development policy in Surakarta. This descriptive qualitative study was obtained from interviews with 8 informants and analyze data from results of interviews, documentation, and observations according aspects of policy formulation process and policy implementation preparation. The findings show that the policy formulation process has through several formulation steps of the Draft Regional Regulation Formulation arranged by the executive and still in the draft has planned to be approved in 2020. Changes of central regulation on tipping fee and concerns about potential state losses had hampered the draft. Eventually, the draft has planned to be finished in 2020 and become regional regulation in 2021 but could not be continued because of the budget was refocusing for Covid-19 handling. Nevertheless, the political will of Surakarta about this matter is very serious. This is realized by taking preparatory steps to implement the policy in parallel with the policy formulation process. In the process of preparing for implementation, the Surakarta City Government has made preparations on organizational activities and interpretations. In organizational activities, designation of the implementor has been carried out institutionally and personally, establishment of implementation management with leading sector and collegial pattern, and the scheduling which is now in the construction phase. While the organizational activity being prepared is making SOP, this is somewhat hampered due to limited resources. In the interpretation activity, Surakarta City Government has not yet fully made official communication and socialization preparations to the residents considering that the implementation is unclear, so that it is still passive to residents around the PLTSa construction.